2015
DOI: 10.1016/j.chembiol.2015.09.017
|View full text |Cite
|
Sign up to set email alerts
|

An L-RNA Aptamer that Binds and Inhibits RNase

Abstract: SUMMARY L-RNA aptamers were developed that bind to barnase ribonuclease and thereby inhibit the function of the enzyme. These aptamers were obtained by first carrying out in vitro selection of D-RNAs that bind to the full-length synthetic D-enantiomer of barnase, then reversing the mirror and preparing L-RNAs of identical sequence that similarly bind to natural L-barnase. The resulting L-aptamers bind L-barnase with an affinity of ~100 nM and function as competitive inhibitors of enzyme cleavage of D-RNA subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 28 publications
(29 reference statements)
1
14
0
Order By: Relevance
“…In a particularly striking example, an aptamer produced by this process was shown to function in the presence of a strong nucleolytic enzyme, demonstrating a critical aspect of biostability 13 . Similar successes have also been achieved using mirror-image aptamers (i.e., spiegelmers) 14 , but such reagents are restricted to achiral targets or targets with mirror-images that can be generated by chemical synthesis 15 . Since XNA aptamers are not restricted in this way, they can be used to target a broader range of biological molecules, most notably large proteins and cells that cannot be produced by chemical synthesis 16 .…”
Section: Introductionmentioning
confidence: 88%
“…In a particularly striking example, an aptamer produced by this process was shown to function in the presence of a strong nucleolytic enzyme, demonstrating a critical aspect of biostability 13 . Similar successes have also been achieved using mirror-image aptamers (i.e., spiegelmers) 14 , but such reagents are restricted to achiral targets or targets with mirror-images that can be generated by chemical synthesis 15 . Since XNA aptamers are not restricted in this way, they can be used to target a broader range of biological molecules, most notably large proteins and cells that cannot be produced by chemical synthesis 16 .…”
Section: Introductionmentioning
confidence: 88%
“…Over the years, studies have demonstrated that L-RNA aptamers can be used to detect small molecules, peptides and proteins ( 23–29 ), and several of them are currently under clinical trials ( 30 ). More recently, L-RNA aptamers that target RNA structure were also reported ( 26 , 31–33 ); however, they are limited to stem–loop/hairpin structured RNA region.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, most of the spiegelmers have been selected for small molecules, cytokines, and peptide hormones [ 7 , 8 , 9 ]. The only published spiegelmer that was isolated using a full-length D-enantiomer protein as target of SELEX (Systematic Evolution of Ligands by EXponential Enrichment) is selective for a small, 110 amino acid-composed RNase, indicating the limits of this approach [ 10 ]. Notwithstanding, the structural analysis of aptamer- and spiegelmer-protein complexes revealed that these oligonucleotides interact with their target through definite amino acid motifs; thus, theoretically protein-selective spiegelmers can be generated without application of D-enantiomers of complete proteins [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%